Introduction to the Special Issue: Highlighting the Best Papers from the OTL SIG AERA 2019 - Swan, Karen; Richardson, Jennifer; Farmer, Tadd (Online Learning, 2019)
At the 2019 annual meeting, the OTL SIG received 145 proposals from which 66 were selected to present. The articles in this special issue report on the research findings stemming from those proposals. It includes several articles concerned with quality in a variety of settings and from both instructor and student perspectives. Instructor perceptions of the development of community and faculty mentoring are also explored, and one paper examines what the instructors of award-winning courses believe makes them award winning. There are also several articles concerned with Massive Open Online Courses (MOOCs). We are also pleased to have the 2019 best paper recipient among the articles collected here.